2021
DOI: 10.1007/s13762-021-03354-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced remediation of pollutants by microorganisms–plant combination

Abstract: The pollutants have become ubiquitous in the total environment (water, soil and air) due to human activities and they are hazardous to all forms of life on the earth. This problem has made scientists focus on mitigating or complete reduction in pollutants by several means. Microorganism and plants are known to scavenge pollutants. Both are studied enormously in reducing, refining, and removing pollutants from the environment successfully. But, their slow process for removal is disadvantage. However, according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 80 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…The initial step to minimizing air pollution is to remove or reduce the source of indoor pollution, like natural and anthropogenic activity, and the second step is to use appropriate and efficient air purification techniques that can remove or detoxify the existing pollutants (Wei et al 2017b). So far, a variety of physiochemical methods or science-based technologies have been effectively implemented for the abatement of indoor air pollution (Wei et al 2017b;Supreeth 2021). But due to the high maintenance costs, these existing conventional remediation technologies need to be replaced by costeffective, eco-friendly, and non-invasive bioremediation approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial step to minimizing air pollution is to remove or reduce the source of indoor pollution, like natural and anthropogenic activity, and the second step is to use appropriate and efficient air purification techniques that can remove or detoxify the existing pollutants (Wei et al 2017b). So far, a variety of physiochemical methods or science-based technologies have been effectively implemented for the abatement of indoor air pollution (Wei et al 2017b;Supreeth 2021). But due to the high maintenance costs, these existing conventional remediation technologies need to be replaced by costeffective, eco-friendly, and non-invasive bioremediation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…But due to the high maintenance costs, these existing conventional remediation technologies need to be replaced by costeffective, eco-friendly, and non-invasive bioremediation approaches. Biological based remediation involves the use of plants and microbes to degrade or transform toxic pollutants into non-toxic ones (Lee et al 2020;Supreeth 2021). A NASA (National Aeronautics and Space Administration) study in space shuttles in 1980 successfully demonstrated the role of plants in airborne pollutants removal (Wolverton et al 1989;Chen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…HXF1 to remove NH 4 + -N from groundwater (Hu et al 2021b). Supreeth reported that plants and bacteria could cooperate to strengthen the removal of NH 4 + -N, total phosphorus (TP), and chemical oxygen demand (COD) (Supreeth 2022). Shen used a microalgae-bacteria system to treat domestic sewage; the results showed that the removal rates of NH 4 + -N, TP, and COD by co-treatment were higher than those by single treatment (Shen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollution is growing rapidly around the world. Heavy metals, pesticides, plasticizers, surfactants, pharmaceuticals, and dyes have been commonly detected in many compartments, such as soil, groundwater or surface water, and air (Hilili et al 2021 ; Singh et al 2021 ; Supreeth 2021 ; Wieczorek et al 2021 ). Many of them are not easily biodegradable and therefore possess long-term persistence in ecosystems (Alharbi et al 2018 ; Kallawar et al 2021 ; Zhang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%